Foreign-Affiliate Activity and U.S. Skill Upgrading - Blonigen, Bruce A.; Slaughter, Matthew J. (The Review of Economics and Statistics, 2001)
There has been little analysis of the impact of inward foreign direct investment (FDI) on U.S. wage inequality, even though the presence of foreign-owned affiliates in the United States has arguably grown more rapidly in significance for the U.S. economy than trade flows. Using U.S. manufacturing data from 1977 to 1994, we find that inward FDI has not contributed to U.S. within-industry skill upgrading. In fact, the 1980s wave of Japanese greenfield investments was significantly correlated with lower, not higher, relative demand for skilled labor. This casts doubt upon one possible channel of skill-biased technological change that was previously unexplored.